Realistic Dilemmas and Path Recommendations for the High-Quality Development of Traditional Chinese Sports - Li, Yan (Quality in Sport, 2025)
Traditional sports culture serves as a significant driving force in the process of building a sports power in China and is a key focus in responding to strategic goals such as Healthy China, national fitness, and rural revitalization. Under the backdrop of building a sports power, how to achieve high-quality development of traditional sports is a major issue concerning the great rejuvenation of the Chinese nation. The research holds that the high-quality development path of traditional sports in our country requires the scientific guidance of the five major concepts of “innovation, coordination, green development, openness and sharing”. Correctly analyze the actual predicament faced: The impact of modern industrial civilization and evolving lifestyles, the contradiction between the weakening sense of belonging to traditional culture and the deepening identification with foreign cultures, as well as the obstacles of low internationalization and poor systematic models. Based on this, explore the necessary path for high-quality development: Relying on the rural revitalization strategy to build new villages dedicated to traditional sports culture; Fostering a strong sense of community for the Chinese nation and enhancing identification with traditional sports culture; Keeping pace with the trend of globalization to create an international brand for traditional sports.